2017
DOI: 10.3758/s13423-016-1127-1
|View full text |Cite
|
Sign up to set email alerts
|

Wondering how: Children’s and adults’ explanations for mundane, improbable, and extraordinary events

Abstract: Children aged 5 through 9 years and adults judged the reality status of parallel mundane, improbable, and extraordinary events, generated an explanation for each event, and evaluated explanations purportedly generated by other participants. Participants of all ages claimed that mundane and improbable events could happen, whereas extraordinary events could not. Participants also overwhelmingly generated natural explanations for all three types of events but did so most for mundane, less for improbable, and leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…For the small number of instances where children judged these stories as 'real', they did not refer to the target cause, and in that sense, did not affirm it as a possible cause. These findings are line with the decades of evidence showing that children rarely invoke supernatural forces as a causal explanation even when faced with unusual or unexpected events (Cornelius, Lacy, & Woolley, 201;Huang, 1930Huang, , 1943Mead;1932;authors, under review) and typically deny the possibility of magical outcomes in real life (Nancekivell & Friedman, 2017;Orozco-Giraldo & Harris, 2019;Subbotsky, 1994Subbotsky, , 2010Woolley & Cornelius, 2017;Woolley & Cox, 2007). Moreover, tempering the earlier conclusions of Corriveau and collegues (Corriveau et al, 2015), we did not find any evidence that exposure to religious testimony renders children more credulous towards the impossible events embedded in magical stories.…”
Section: Discussionsupporting
confidence: 81%
“…For the small number of instances where children judged these stories as 'real', they did not refer to the target cause, and in that sense, did not affirm it as a possible cause. These findings are line with the decades of evidence showing that children rarely invoke supernatural forces as a causal explanation even when faced with unusual or unexpected events (Cornelius, Lacy, & Woolley, 201;Huang, 1930Huang, , 1943Mead;1932;authors, under review) and typically deny the possibility of magical outcomes in real life (Nancekivell & Friedman, 2017;Orozco-Giraldo & Harris, 2019;Subbotsky, 1994Subbotsky, , 2010Woolley & Cornelius, 2017;Woolley & Cox, 2007). Moreover, tempering the earlier conclusions of Corriveau and collegues (Corriveau et al, 2015), we did not find any evidence that exposure to religious testimony renders children more credulous towards the impossible events embedded in magical stories.…”
Section: Discussionsupporting
confidence: 81%
“…Even when Nancekivell and Friedman (2017) included a magical being (e.g., a fairy or wizard) in the story, children still provided natural explanations for the phenomena. Woolley and Cornelius (2017) further found that children's belief about the possibility of supernatural events was related to their explanations for those events. Although 5-to 9-year-olds were most likely to give natural explanations for how three kinds of events could have happened [mundane (i.e., a boy bumps a vase and returns it to the shelf and the mom doesn't notice), improbable (i.e., the vase breaks, the boy fixes it and the mom doesn't notice), or extraordinary (i.e., the vase breaks and is fixed when the boy looks up from hiding behind the couch)], when children claimed the extraordinary event was possible, they also were more likely to give a supernatural explanation (e.g., God or magic) for that event.…”
Section: Developing Understanding Of Improbable and Impossible Eventsmentioning
confidence: 91%
“…To examine the ontological status of people’s beliefs, participants’ explanations were classified using a coding scheme that was adapted from Woolley and Cornelius (2017). Explanations were coded as natural when the participant alluded to physical, biological, chemical, or psychological processes (e.g., “People can detect pheromones and react emotionally based off of them.” [T-shirt—joy]; “Religious water doesn’t have any medical healing powers so it would be the placebo effect.” [anointed water]).…”
Section: Resultsmentioning
confidence: 99%